Comparative analysis of data mining techniques for medical data classification - S. A., Lashari; Ibrahim, Rosziati (2013)
Medical data classification plays a crucial role in many medical imaging applications by automating or facilitating the delineation of image data.It addresses the problem of diagnosis, analysis and teaching purposes in medicine.For these several medical imaging data modalities and applications based on data mining techniques have been proposed and developed.In this paper, a comparative analysis of applications of data mining techniques has been presented.Thus, the existing literature suggests that we do not lose sight of the current and future potential of applications of data mining techniques that can impact upon the successful classification of medical data into a thematic map.Thus, there is a great potential for the use of data mining techniques for medical data classification, which has not been fully investigated and would be one of the interesting directions for future research.